Developing an Optimal Antiviral Method for the Air-filtration System of Subway Stations - Dae Hoon Park; Jungho Hwang; Dongho Shin; Younghun Kim; Gunhee Lee; Inyong Park; Sang Bok Kim; Keejung Hong; Bangwoo Han (Aerosol and Air Quality Research)
Abstract A novel antiviral method was developed in this study for the air-filtration system of subway stations. Using a dry aerosol coating process, along with a spark discharger and carbon-brush-type ionizer, we developed a high-performance antiviral air filter. Herein, Ag nanoparticles were produced using a spark–discharge generation system with an ion-injection system and were employed as antiviral agents for coating onto a medium-grade air filter. Moreover, we tested the pressure drop in the filter as well as its filtration efficiency and antiviral ability against aerosolized bacteriophage MS2 virus particles as a surrogate of the severe acute respiratory syndrome coronavirus 2 during dust loading. Notably, the dust contamination caused an increase in the filtration efficiency and pressure drop, whereas the antiviral agents (herein, the Ag nanoparticles) did not have a significant effect in this regard. Based on this, we suggested a novel method to regenerate the antiviral effect of the antiviral air filter contaminated by the dust particles. Furthermore, a theoretical analysis of the antiviral ability and antiviral effect regeneration for the case of dust loading was performed using a mathematical model to evaluate the time-dependent antiviral effect of the filter. Our model can be applied to the antiviral air-filtration system of subway stations to prevent the pandemic spread and predict the life cycle of antiviral filters.